2020
DOI: 10.1136/bmjstel-2019-000517
|View full text |Cite
|
Sign up to set email alerts
|

Use of functional near-infrared spectroscopy to evaluate cognitive change when using healthcare simulation tools

Abstract: BackgroundThe use of brain imaging techniques in healthcare simulation is relatively rare. However, the use of mobile, wireless technique, such as functional near-infrared spectroscopy (fNIRS), is becoming a useful tool for assessing the unique demands of simulation learning. For this study, this imaging technique was used to evaluate cognitive load during simulation learning events.MethodsThis study took place in relation to six simulation activities, paired for similarity, and evaluated comparative cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Li et al [ 25 ] mixed simulated driving with n -back tasks to validate that fNIRS is sensitive to workload changes in rail transit drivers. Taylor et al [ 26 ] compared healthcare employees’ performance of tasks under varying conditions, e.g., performing a handoff in-person or over video. They concluded that fNIRS was a useful tool in measuring cognitive load, and that load increased with task complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 25 ] mixed simulated driving with n -back tasks to validate that fNIRS is sensitive to workload changes in rail transit drivers. Taylor et al [ 26 ] compared healthcare employees’ performance of tasks under varying conditions, e.g., performing a handoff in-person or over video. They concluded that fNIRS was a useful tool in measuring cognitive load, and that load increased with task complexity.…”
Section: Discussionmentioning
confidence: 99%